Phylogenetic analysis of respiratory syncytial virus identified at universiti kebangsaan Malaysia medical centre - Rahman M.M.; Wong K.K.; Isahak I.; Rashid Z.Z.; Alfizah H. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Human respiratory syncytial virus (RSV) is an important cause of acute respiratory tract infection in infants and young children. Phylogenetic analysis for RSV in Malaysia has not been reported before. We investigated the genetic features of RSV in respiratory specimens from March to August 2011 with molecular methods. From a total of 130 throat swab and nasopharyngeal aspirate specimens, 54 (41.5%) were positive with RSV, identified by in-house real-time reverse transcriptase polymerase chain reaction (rRT-PCR) assay. Thirty-four out of 54 (63.0%) RSV positive patients were children below two years old and two (1.4%) were adults. Phylogenetic analysis showed 39 isolates were genotype GA5, 13 genotypes GA2, one genotype GA1 and one genotype GA7. The findings indicated four genotypes of RSV circulating in the country and the predominant genotype is GA5.